2014
DOI: 10.1590/1981-8637201400020000081192
|View full text |Cite
|
Sign up to set email alerts
|

Perception assessment of periodontal patients regarding their self-care

Abstract: OBJECTIVE: The aim of this study is to evaluate, through a questionnaire, patients' awareness and behavior regarding periodontal disease, as well as their perceptions of the importance of self-care in order to control the disease. METHODS: 50 male and female patients, age ranging between 31 to 67 years old, presenting moderate to advanced periodontal disease were submitted to a 26 question-survey which aimed to assess the following: the patient's profile, his knowledge and awareness of the periodontal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…This study further demonstrates that explanation from dental professionals is crucial to establishing rapport with patients and motivation for oral hygiene maintenance. The instructions must be in plain and comprehensible language appropriate to the patient's age and cultural level [18].…”
Section: Discussionmentioning
confidence: 99%
“…This study further demonstrates that explanation from dental professionals is crucial to establishing rapport with patients and motivation for oral hygiene maintenance. The instructions must be in plain and comprehensible language appropriate to the patient's age and cultural level [18].…”
Section: Discussionmentioning
confidence: 99%
“…14 Majority of the participants (52%) reported that they brush once daily on regular bases whereas a study conducted in Sao Pualo reported that 56% participants brush their teeth trice a day. 18 72% participants reported that they chance their brush every 3months. Horizontal brushing technique was reported by majority of participants (58%).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of current study reported that majority of patients (52%) reported their oral health as fair whereas literature reported that 40% of the population of a study perceived their oral health as fair. 18 A modified self-report questionnaire represents a valuable and adequate tool for the screening and surveillance of periodontitis at the population level. Similar studies need to be conducted for the Pakistani population generally and efforts should be made to give better awareness to the patients about disease…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, conforme esperado, as variáveis comportamentais relacionadas ao cuidado com a higiene bucal (autocuidado regular e higiene bucal orientada) se confirmaram como fatores de proteção para a doença periodontal. O impacto da Higiene Bucal Orientada sobre a condição periodontal foi abordado por Garcia et al 25 em um estudo que avaliou a percepção dos pacientes periodontais a respeito de seu autocuidado, o qual concluiu que os pacientes se tornam mais motivados para a higiene bucal quando o cirurgião-dentista promove instrução apropriada.…”
Section: Discussionunclassified